Isolation and Characterization of Multidrug-resistant Enterobacteriaceae from Kitchen Sponges: An Under-recognized Public Health Problem - Ikechukwu Benjamin Moses; Clinton Okwudili Mbam; Cynthia Ogochukwu Odi; Mustofa Helmi Effendi; Aswin Rafif Khairullah; Adiana Mutamsari Witaningrum; Boniface Oke; Moses Chukwuemeka Ezea; Saifur Rehman (Indian Journal of Public Health)
Background: The domestic kitchen is increasingly being recognized as one of the most important areas with regards to the incidences of foodborne diseases. Kitchen sponges may play a role in foodborne illnesses through cross-contamination as they provide a suitable environment for bacterial pathogen growth and transmission. Objectives: This study was designed to isolate, characterize, and determine the antibiogram of Enterobacteriaceae contaminating household kitchen sponges in Abakaliki metropolis, Nigeria. Materials and Methods: A total of 50 household kitchen sponges were randomly collected from 50 different households in Abakaliki metropolis. The samples were analyzed with standard microbiological techniques and antimicrobial susceptibility testing was done by the disc diffusion method. Results: In total, 28 (56%) out of the 50 kitchen sponges were positive for Salmonella spp. (10), Klebsiella spp. (7), and Escherichia coli (11). In general, isolates were multidrug-resistant with high resistance frequencies (43.7%–100%) to carbapenems, aztreonam, tetracycline, amoxicillin-clavulanic acid, cephalosporins, and sulfamethoxazole-trimethoprim. There was no statistically significant difference in the antimicrobial resistance frequencies between the Enterobacteriaceae isolates (P = 0.982). The multiple antibiotics resistance index values of isolates ranged from 0.4 to 0.8. Conclusion: This study has shown that household kitchen sponges are highly contaminated by multidrug-resistant Klebsiella spp., Salmonella spp., and E. coli. The contamination of household kitchen sponges by these multidrug-resistant bacterial pathogens is a serious public health problem that requires urgent attention. It is therefore of utmost importance to properly wash and disinfect household kitchen sponges after their use, in order to prevent the spread of difficult-to-treat microbial infections.